The effect of self-regulated learning strategies on the primary school students' independent learning skill - Sukowati Sukowati; E. Kus Eddy Sartono; Gunarti Ika Pradewi (Psychology, Evaluation, and Technology in Educational Research, 2020)
Students have Self-Regulated Learning (SRL) which can motivate themselves to arrange personal goals, plan strategies done to achieve the goal, until to evaluate the behaviors. Besides that, students can be more responsible to themselves so that the learning independence of students can be formed. This research aimed to investigate the level of SRL and learning independence of elementary school students, and to investigate the influence of SRL towards the learning independence of elementary school students. This research used a quantitative approach with the comparative research design. The population in this research was 387 students with the sample used was 194 students taken randomly using Slovin’s formula. The instrument used in this research consisted of 24 questions by using 4-point Likert Scale. The data collection technique was used by comparing SRL of students. The data analysis was conducted by SPSS version 24. The finding of the research showed that SLR and learning independence of elementary school students was on the category medium and has a tcount of 8,516. In addition, the F-test result obtained was 240, 783. Therefore, it can be concluded that there is a significant influence between SRL and the learning independence of elementary school students. The futher reasearch must be based on previous studies. The influence of SRL on student independence and the factors that influence needed to described more comperhensive.